PENCEGAHAN DEKUBITUS PASIEN STROKE HEMORRHAGIC SETELAH 24 JAM SERANGAN DI STROKE CENTER RSUD NGUDI WALUYO WLINGI - Rachmawati, Dewi; Ulum, Etika Ma'rifatul; Septdianto, Tri Cahyo (School of Nursing, Faculty of Medicine and Health Science, Universitas Lambung Mangkurat, 2019)
Stroke is a major cause of death and disability with a disease burden that has doubled inIndonesia. The high rate of disability prolongs treatment time and bed rest so that the risk ofdecubitus sores is high if 24-48 hours post attack is not immediately carried out earlymobilization. Objective this study to describe prevention of pressure ulcer hemorrhagic strokepatient on 24-hour post attack. This case study uses a nursing care approach. The subjects werehemorrhagic stroke patients on 24-hour post attack and their families with decubitus risk nursingproblems. Data collection uses interviews, observation, physical examination, and assessment ofthe risk of decubitus with Norton scale. Nursing actions are carried out giving bedmobilization/transfer every 2 hours and skin massage in the depressed area. The results of thestudy show administration of bed rest/mobilization every 2 hours and administration of skinmassage in the depressed area proved effective in reducing the risk of decubitus as evidenced bythe increase in Norton scale scores. It is expected that nurses/families apply bed rest/mobilizationevery 2 hours and skin massage in depressed areas as early as possible for pressure soresprevention.